Waterproof fire-retardant compact environment-friendly diatom functional plate and preparation method thereof

CN120794502BActive Publication Date: 2026-10-27FOSHAN SANSHUI XIANGRUN PACKAGING MATERIALS CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511102639.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-07
Publication Date
2026-10-27
Estimated Expiration
2045-08-07

AI Technical Summary

Technical Problem

[0004]但是上述方案虽然优化了原料配比,引入改性硅藻土和秸秆等提升功能,但是未解决微裂纹自修复问题,长期使用中易因外力或温湿度变化产生裂纹,导致防水、阻燃性能下降;原料中缺乏对工业固废的高效利用,且纤维改性方式单一,难以充分发挥增强与耐水协同作用;工艺上未针对致密性与功能保留的平衡进行优化,孔隙率控制不佳,影响防水与强度的协同提升

Benefits of technology

脱模后将板材置于温度20-25℃,湿度50%-60%通风干燥区自然干燥36-72h,控制干燥速率≤0.5%/h,避免快速干燥导致开裂,确保尺寸稳定性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120794502B_ABST
    Figure CN120794502B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of diatom plate preparation, and particularly relates to a waterproof and flame-retardant compact environment-friendly diatom functional plate and a preparation method thereof, which comprises the following components in parts by weight: graphene modified diatomite 38-55 parts, silicate cement 12-22 parts, bentonite 6-9 parts, steel slag micro powder 4-7 parts, metakaolin 5-8 parts, modified rice hull fiber 3-6 parts, aluminum hydroxide 4-6 parts, polysiloxane repairing agent 1-2 parts, sodium carboxymethyl cellulose 0.8-1.5 parts, defoaming agent 0.5-1 part, and nano zinc oxide 1-2 parts. The present application solves the contradiction between flame retardation and heat dissipation in the reference material by the synergistic effect of graphene modified diatomite and aluminum hydroxide, which improves the flame-retardant performance and avoids local high-temperature accumulation by the heat conduction characteristics of graphene. The sodium modified bentonite and polysiloxane repairing agent are introduced to realize the micro-crack self-repairing function, which makes up for the defect of traditional diatom plates without self-repairing ability and prolongs the service life of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of diatomaceous earth board preparation technology, specifically to a waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board and its preparation method. Background Technology

[0002] In the current construction field, diatomaceous earth-based panels have shown application potential in thermal insulation and humidity control due to the porous nature of diatomaceous earth. However, there are still many limitations in actual use. Traditional diatomaceous earth panels mostly rely on a simple composite of diatomaceous earth and cement, which is not dense enough and is prone to structural deformation due to water absorption. Its waterproof performance is also difficult to meet the requirements of humid environments. Although the flame retardant performance has been improved by adding mineral flame retardants, it often conflicts with the strength of the panel, making it difficult to achieve both high-efficiency flame retardancy and mechanical stability.

[0003] For example, the invention patent publication number CN113045265A discloses a multifunctional diatomaceous earth board with moisture-proof, water-resistant, flame-retardant, and environmentally friendly properties, and its preparation method. This diatomaceous earth board is made from the following raw materials in parts by weight: 35-65 parts modified diatomaceous earth, 10-25 parts cement, 3-5 parts boron ore, 3-5 parts clay, 5-7 parts silica, 2-6 parts calcite, 3-7 parts modified straw, 1-2 parts polyethylene wax, 1-2 parts polycarboxylate superplasticizer, 0.5-1 part photocatalyst, 1-3 parts defoamer, and 0.5-1 part polishing agent. The raw materials provided for this diatomaceous earth board are sourced from abundant mineral resources, promoting resource reuse.

[0004] However, although the above solutions optimized the raw material ratio and introduced modified diatomaceous earth and straw to enhance functionality, they did not solve the problem of microcrack self-repair. During long-term use, cracks are easily generated due to external forces or changes in temperature and humidity, leading to a decline in waterproof and flame-retardant performance. The raw materials lack efficient utilization of industrial solid waste, and the fiber modification method is singular, making it difficult to fully exert the synergistic effect of reinforcement and water resistance. In terms of process, the balance between density and functional retention has not been optimized, and the porosity control is poor, affecting the synergistic improvement of waterproof and strength. Summary of the Invention

[0005] This invention addresses the technical problems existing in the prior art by providing a waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board and its preparation method.

[0006] The technical solution of this invention to solve the above-mentioned technical problems is as follows: A waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board, comprising the following components by weight: The composition includes: 38-55 parts graphene-modified diatomaceous earth, 12-22 parts silicate cement, 6-9 parts bentonite, 4-7 parts steel slag powder, 5-8 parts metakaolin, 3-6 parts modified rice husk fiber, 4-6 parts aluminum hydroxide, 1-2 parts polysiloxane repair agent, 0.8-1.5 parts sodium carboxymethyl cellulose, 0.5-1 part defoamer, and 1-2 parts nano zinc oxide. The graphene-modified diatomaceous earth comprises diatomaceous earth and graphene in a mass ratio of 100:2, and 0.3% titanate coupling agent. The modified rice husk fiber comprises lignin- and pectin-free rice husk fiber, 1.5% sodium hydroxide, and 0.5% silane coupling agent. The matrix material is composed of graphene-modified diatomaceous earth, silicate cement, steel slag powder, and metakaolin, while the reinforcing material is composed of activated bentonite, aluminum hydroxide, and modified rice husk fiber.

[0007] In a preferred embodiment, the diatomaceous earth functional board further includes the following specific components: The ingredients are: 50 parts graphene-modified diatomaceous earth, 18 parts silicate cement, 8 parts bentonite, 6 parts steel slag powder, 7 parts metakaolin, 5 parts modified rice husk fiber, 5 parts aluminum hydroxide, 1.5 parts polysiloxane repair agent, 1.2 parts sodium carboxymethyl cellulose, 0.5 parts defoamer, and 1.5 parts nano zinc oxide.

[0008] In a preferred embodiment, the graphene-modified diatomaceous earth has a specific surface area ≥130 m². 2 / g, the moisture swelling rate of the modified rice husk fiber is ≤0.12%.

[0009] This invention also provides a method for preparing a waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board. The method includes: using diatomaceous earth ore and graphene as substrates, preparing graphene-modified diatomaceous earth by modification with 0.3% titanate coupling agent; alkali-treating the surface of rice husk fibers; preparing modified rice husk fibers with 0.5% silane coupling agent; using calcium-based bentonite as a substrate, modifying it with sodium and then granulating it; using magnetically separated steelmaking waste slag as a substrate, preparing steel slag micropowder through pretreatment; and preparing the resulting product through mixing and molding curing to obtain the diatomaceous earth functional board. The method also includes the following sub-steps: S101. After crushing the raw diatomite ore, it is initially ground. The initial ground diatomite and graphene are added at a mass ratio of 100:2 and mixed until the graphene adheres to the initial ground diatomite. 0.3% titanate coupling agent and deionized water are added, and the mixture is ultrasonically dispersed. The suspension is dried by a dryer to obtain composite powder. S102. After removing impurities, washing and drying the waste rice husks, crush them into fiber segments, add 1.5% sodium hydroxide to remove surface lignin and pectin, wash and add 0.5% silane coupling agent for modification, ultrasonic treatment, dry and crush again to obtain modified rice husk fiber. S103. After crushing the calcium-based bentonite ore, add 3% sodium carbonate solution, filter to obtain filter cake, add 0.3% polyvinyl alcohol solution to granulate, and obtain activated bentonite. S104. Steelmaking waste slag is magnetically separated to remove iron, then crushed, added with 5% sulfuric acid solution, acid washed, and then added with triethanolamine and stirred to obtain steel slag powder. S105. The obtained dry powder, reinforcing material, liquid and additives are added in sequence and dispersed by ultrasonication to obtain a slurry. The slurry is then degassed by vacuum, rolled and cured.

[0010] In a preferred embodiment, the preparation of graphene-modified diatomaceous earth using diatomaceous earth ore and graphene as substrates, modified with 0.3% titanate coupling agent, further includes: After crushing the raw diatomite ore, the particle size obtained is ≤5mm. It is then initially ground to 300 mesh using a grinding mill to remove impurities and improve initial dispersibility. The added graphene sheets have a diameter of 5-10 μm and a thickness of 0.8-1.2 nm; The diatomaceous earth and graphene are mixed at 2000-5000 rpm for 5-10 min to obtain a mixed powder in which graphene is attached to the diatomaceous earth. This pre-disperses the graphene and prevents agglomeration. The mixed powder, prepared with 0.3% titanate coupling agent and deionized water, is a 30-40% suspension. The ultrasonic treatment lasts for 30-45 minutes. Through the chemical bonding effect of the coupling agent, the interfacial bonding force between graphene and diatomaceous earth is strengthened. The suspension was dried in a spray dryer, and the resulting composite powder was pulverized by airflow with an air pressure of 1.1-1.3 MPa. Graphene-modified diatomaceous earth with a mesh size of 1200-1500 was screened to refine the particle size to a controllable range of nanoscale pores and increase the specific surface area to ≥130 m² / g.

[0011] Furthermore, the graphene selected in this application has high electrical and thermal conductivity, which can accelerate heat diffusion and prevent local high temperature ignition; at the same time, the graphene sheets block oxygen from contacting combustibles, synergistically improving flame retardant performance. After modification with coupling agent, the compatibility between graphene and diatomaceous earth interface is improved, solving the problem of easy graphene agglomeration and ensuring that it is uniformly dispersed in the matrix.

[0012] In a preferred embodiment, the alkali treatment of the rice husk fiber surface to prepare modified rice husk fibers using 0.5% silane coupling agent further includes: The waste rice husks, after being cleaned and purified, are dried in an oven at 90-105℃ until the moisture content is ≤5%. The fiber segments are then shredded by a shredder to a length of 5-10mm to remove surface impurities and reduce the impact of fiber moisture content on the strength of the board. Add 1.5% sodium hydroxide solution to the fiber segment at a solid-liquid ratio of 1:10, and stir and cook in a water bath at 60-80℃ for 25-40 minutes to enhance the surface activity of the fiber and increase the bonding sites with the inorganic matrix. Wash the fiber segments with deionized water at pH 7 until they are neutral. After filtration, add 0.5% silane coupling agent at a solid-liquid ratio of 1:8. Sonicate for 20-30 minutes, dry at 45-60℃, and then pulverize the fiber segments to a mesh size greater than 350. The coupling agent forms an organic-inorganic transition layer on the fiber surface, which strengthens the interfacial bonding between the fiber and cement and diatomaceous earth.

[0013] Furthermore, this application increases the surface roughness of rice husk fibers after alkali treatment, thereby enhancing the mechanical interlocking force with the matrix and improving the flexural strength of the board. After modification with silane coupling agent, the water resistance of the fibers is improved, preventing the board from cracking due to water absorption and expansion.

[0014] In a preferred embodiment, the granulation process following sodium modification of the calcium-based bentonite substrate further includes: The calcium-based bentonite ore is crushed and sieved through a 200-mesh sieve. A 3% sodium carbonate solution is added at a solid-liquid ratio of 1:6, and the mixture is stirred at 50-60℃ for 2-4 hours for sodium modification, converting the calcium-based bentonite into sodium-based bentonite and improving its water absorption and swelling properties. The mixture is allowed to settle for 3-4 hours, and the filter cake is filtered. The mixture is then dried at 70-80℃ and pulverized to 300 mesh. Finally, a 0.3% polyvinyl alcohol solution is added at a solid-liquid ratio of 1:5, and the mixture is granulated to improve the uniformity of bentonite dispersion in the mixture. Furthermore, after sodium modification, the water absorption and swelling ratio of bentonite increases from 5-8 times that of the original ore to 15-20 times. It can quickly absorb water and expand when microcracks occur in the board, fill the crack gaps and achieve self-repair. Granulation treatment avoids bentonite agglomeration and ensures that it is evenly distributed in the matrix, thus improving the self-repair efficiency. When the width of microcracks is ≤0.2mm, it can be completely repaired.

[0015] In a preferred embodiment, the step of preparing steel slag powder through pretreatment using magnetically separated steelmaking waste slag as a substrate further includes: Steelmaking waste slag after magnetic separation and iron removal is crushed to 400 mesh, soaked in 5% sulfuric acid solution at a ratio of 1:4 for 1-3 hours to remove free calcium and impurities on the surface, reducing the risk of poor potential volume stability of steel slag. After acid washing, it is washed with deionized water until neutral, dried at 100-115℃ and 0.2% triethanolamine is added and stirred for 4-12 minutes to promote the hydration reaction of active components in steel slag and enhance its strength contribution. Furthermore, pretreated steel slag powder can replace calcite as a filler, reducing raw material costs while realizing the resource utilization of industrial solid waste.

[0016] In a preferred embodiment, the obtained product undergoes mixture preparation and molding curing, including: Graphene-modified diatomaceous earth, ordinary silicate cement, steel slag powder, and metakaolin are added to a twin-shaft mixer and stirred at 100-300 r / min for 5-10 minutes at room temperature to ensure uniform dispersion of inorganic powders, uniform mixing of matrix skeleton materials, and reduced strength fluctuations. Add activated bentonite, aluminum hydroxide, and modified rice husk fiber. Adjust the speed to 200-400 r / min and continue stirring for 2-5 min. The bentonite and aluminum hydroxide form a synergistic flame retardant system, and the fiber constructs a three-dimensional reinforcing network. Add polysiloxane repair agent, sodium carboxymethyl cellulose, and nano zinc oxide, and add 40-48% deionized water by weight. Heat to 55-60℃ and stir at 100-200 r / min for 15 min. Sodium carboxymethyl cellulose improves the water retention of the slurry, and polysiloxane enhances the waterproofness of the interface. The mixture is transferred to an ultrasonic dispersion device and treated with 200-300W power for 5-10 minutes to obtain a slurry. This process breaks up air bubbles and agglomerates in the slurry, allowing the nano-zinc oxide and graphene to be evenly dispersed, thus improving antibacterial and thermal conductivity properties. Stepwise stirring avoids reaction conflicts between materials and ensures the uniform distribution of functional materials such as bentonite and fibers. After ultrasonic treatment, the porosity of the mixture is reduced to below 8%, laying the foundation for the densification of the board and improving the interfacial bonding between the flame retardant and the matrix.

[0017] In a preferred embodiment, it further includes: The slurry is injected into a vacuum degasser and treated at a vacuum of -0.09MPa for 4-5 minutes to remove air bubbles trapped in the slurry, reduce the internal pores of the board after molding, and improve the density and water resistance. The slurry is then pressed into a wet board blank by three rollers. The wet slurry blank is transferred to the curing room and left to stand for 2 hours at 20-25℃ and 30-70% relative humidity, so that the bentonite can initially absorb water and expand to fill the micropores inside the blank. Adjust the temperature of the curing room to 60-80℃ and the relative humidity to 80-90%, and perform hydrothermal curing for 2-4 hours to accelerate the hydration reaction of cement and steel slag powder, generate more CSH gel, and improve the strength of the matrix. After demolding, place the board in a well-ventilated drying area with a temperature of 20-25℃ and a humidity of 50%-60% to air dry naturally for 36-72 hours. Control the drying rate to ≤0.5% / h to avoid cracking caused by rapid drying and ensure dimensional stability. After drying, a 0.2-0.5mm thick silane waterproofing agent is sprayed onto the surface of the board and cured at room temperature for 12-24 hours to form a hydrophobic film on the surface, further improving the waterproof performance and reducing the water absorption rate.

[0018] The beneficial effects of this invention are: through the synergistic effect of graphene-modified diatomaceous earth and aluminum hydroxide, the flame retardant performance is improved, while the thermal conductivity of graphene is used to avoid local high temperature accumulation, thus solving the contradiction between flame retardancy and heat dissipation in the reference materials. The introduction of sodium-modified bentonite and polysiloxane repair agent realizes the self-repair function of microcracks, making up for the defect of traditional diatomaceous earth boards having no self-repair ability and extending the service life of the material. Pre-treating steelmaking waste slag into steel slag powder to replace traditional fillers, and using waste rice husk fiber as a reinforcing material after alkali treatment and silane modification, significantly improves the resource utilization rate of industrial and agricultural solid waste. Compared with the single straw utilization in the reference materials, the types of solid waste are wider and the utilization efficiency is higher. Attached Figure Description

[0019] Figure 1 The flowchart is for the preparation of this invention. Detailed Implementation

[0020] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0021] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the stated features. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0022] In the description of this application, the term "for example" is used to mean "used as an example, illustration, or description." Any embodiment described as "for example" in this application is not necessarily to be construed as being more preferred or advantageous than other embodiments. The following description is provided to enable any person skilled in the art to make and use the invention. Details are set forth in the following description for purposes of explanation. It should be understood that those skilled in the art will recognize that the invention can be made without using these specific details. In other instances, well-known structures and processes will not be described in detail to avoid obscuring the description of the invention with unnecessary detail. Therefore, the invention is not intended to be limited to the embodiments shown, but is consistent with the broadest scope of the principles and features disclosed in this application.

[0023] This embodiment provides a method for preparing a waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board, comprising the following steps: Using diatomaceous earth ore and graphene as substrates, graphene-modified diatomaceous earth is prepared by modification with 0.3% titanate coupling agent. The surface of rice husk fibers is treated with alkali, and modified rice husk fibers are prepared with 0.5% silane coupling agent. Calcium-based bentonite is used as a substrate and modified by sodium treatment, followed by granulation. Steel slag powder is prepared by pretreatment using magnetically separated steelmaking waste slag as a substrate. The resulting products are then mixed and molded to obtain a diatomaceous earth functional board. The process also includes the following sub-steps: S101. After crushing the raw diatomite ore, it is initially ground. The initial ground diatomite and graphene are added at a mass ratio of 100:2 and mixed until the graphene adheres to the initial ground diatomite. 0.3% titanate coupling agent and deionized water are added, and the mixture is ultrasonically dispersed. The suspension is dried by a dryer to obtain composite powder. Graphene-modified diatomaceous earth was prepared by modifying diatomaceous earth with 0.3% titanate coupling agent using diatomaceous earth ore and graphene as substrates. The preparation also includes: After crushing the raw diatomite ore, the particle size obtained is ≤5mm. It is then initially ground to 300 mesh using a grinding mill to remove impurities and improve initial dispersibility. The added graphene sheets have a diameter of 5-10 μm and a thickness of 0.8-1.2 nm; The diatomaceous earth and graphene are mixed at 2000-5000 rpm for 5-10 min to obtain a mixed powder in which graphene is attached to the diatomaceous earth. This pre-disperses the graphene and prevents agglomeration. The mixed powder, prepared with 0.3% titanate coupling agent and deionized water, is a 30-40% suspension. The ultrasonic treatment lasts for 30-45 minutes. Through the chemical bonding effect of the coupling agent, the interfacial bonding force between graphene and diatomaceous earth is strengthened. The suspension was dried in a spray dryer, and the resulting composite powder was pulverized by airflow with an air pressure of 1.1-1.3 MPa. Graphene-modified diatomaceous earth with a mesh size of 1200-1500 was screened to refine the particle size to a controllable range of nanoscale pores and increase the specific surface area to ≥130 m² / g.

[0024] Furthermore, the graphene selected in this application has high electrical and thermal conductivity, which can accelerate heat diffusion and prevent local high temperature ignition; at the same time, the graphene sheets block oxygen from contacting combustibles, synergistically improving flame retardant performance. After modification with coupling agent, the compatibility between graphene and diatomaceous earth interface is improved, solving the problem of easy graphene agglomeration and ensuring that it is uniformly dispersed in the matrix.

[0025] S102. After removing impurities, washing and drying the waste rice husks, crush them into fiber segments, add 1.5% sodium hydroxide to remove surface lignin and pectin, wash and add 0.5% silane coupling agent for modification, ultrasonic treatment, dry and crush again to obtain modified rice husk fiber. Alkali treatment of rice husk fiber surface, followed by preparation of modified rice husk fiber using 0.5% silane coupling agent, also includes: The waste rice husks, after being cleaned and purified, are dried in an oven at 90-105℃ until the moisture content is ≤5%. The fiber segments are then shredded by a shredder to a length of 5-10mm to remove surface impurities and reduce the impact of fiber moisture content on the strength of the board. Add 1.5% sodium hydroxide solution to the fiber segment at a solid-liquid ratio of 1:10, and stir and cook in a water bath at 60-80℃ for 25-40 minutes to enhance the surface activity of the fiber and increase the bonding sites with the inorganic matrix. Wash the fiber segments with deionized water at pH 7 until they are neutral. After filtration, add 0.5% silane coupling agent at a solid-liquid ratio of 1:8. Sonicate for 20-30 minutes, dry at 45-60℃, and then pulverize the fiber segments to a mesh size greater than 350. The coupling agent forms an organic-inorganic transition layer on the fiber surface, which strengthens the interfacial bonding between the fiber and cement and diatomaceous earth.

[0026] Furthermore, this application increases the surface roughness of rice husk fibers after alkali treatment, thereby enhancing the mechanical interlocking force with the matrix and improving the flexural strength of the board. After modification with silane coupling agent, the water resistance of the fibers is improved, preventing the board from cracking due to water absorption and expansion.

[0027] S103. After crushing the calcium-based bentonite ore, add 3% sodium carbonate solution, filter to obtain filter cake, add 0.3% polyvinyl alcohol solution to granulate, and obtain activated bentonite. The process of using calcium-based bentonite as a substrate, after sodium modification and granulation, also includes: The calcium-based bentonite ore is crushed and sieved through a 200-mesh sieve. A 3% sodium carbonate solution is added at a solid-liquid ratio of 1:6, and the mixture is stirred at 50-60℃ for 2-4 hours for sodium modification, converting the calcium-based bentonite into sodium-based bentonite and improving its water absorption and swelling properties. The mixture is allowed to settle for 3-4 hours, and the filter cake is filtered. The mixture is then dried at 70-80℃ and pulverized to 300 mesh. Finally, a 0.3% polyvinyl alcohol solution is added at a solid-liquid ratio of 1:5, and the mixture is granulated to improve the uniformity of bentonite dispersion in the mixture. Furthermore, after sodium modification, the water absorption and swelling ratio of bentonite increases from 5-8 times that of the original ore to 15-20 times. It can quickly absorb water and expand when microcracks occur in the board, fill the crack gaps and achieve self-repair. Granulation treatment avoids bentonite agglomeration and ensures that it is evenly distributed in the matrix, thus improving the self-repair efficiency. When the width of microcracks is ≤0.2mm, it can be completely repaired.

[0028] S104. Steelmaking waste slag is magnetically separated to remove iron, then crushed, added with 5% sulfuric acid solution, acid washed, and then added with triethanolamine and stirred to obtain steel slag powder. Using magnetically separated steelmaking waste slag as a base material, steel slag powder is prepared through pretreatment, which also includes: Steelmaking waste slag after magnetic separation and iron removal is crushed to 400 mesh, soaked in 5% sulfuric acid solution at a ratio of 1:4 for 1-3 hours to remove free calcium and impurities on the surface, reducing the risk of poor potential volume stability of steel slag. After acid washing, it is washed with deionized water until neutral, dried at 100-115℃ and 0.2% triethanolamine is added and stirred for 4-12 minutes to promote the hydration reaction of active components in steel slag and enhance its strength contribution. Furthermore, pretreated steel slag powder can replace calcite as a filler, reducing raw material costs while realizing the resource utilization of industrial solid waste.

[0029] S105. The obtained dry powder, reinforcing material, liquid and additives are added in sequence and dispersed by ultrasonication to obtain a slurry. The slurry is then degassed by vacuum, rolled and cured.

[0030] The resulting product undergoes mixture preparation and molding curing, including: Graphene-modified diatomaceous earth, ordinary silicate cement, steel slag powder, and metakaolin are added to a twin-shaft mixer and stirred at 100-300 r / min for 5-10 minutes at room temperature to ensure uniform dispersion of inorganic powders, uniform mixing of matrix skeleton materials, and reduced strength fluctuations. Add activated bentonite, aluminum hydroxide, and modified rice husk fiber. Adjust the speed to 200-400 r / min and continue stirring for 2-5 min. The bentonite and aluminum hydroxide form a synergistic flame retardant system, and the fiber constructs a three-dimensional reinforcing network. Add polysiloxane repair agent, sodium carboxymethyl cellulose, and nano zinc oxide, and add 40-48% deionized water by weight. Heat to 55-60℃ and stir at 100-200 r / min for 15 min. Sodium carboxymethyl cellulose improves the water retention of the slurry, and polysiloxane enhances the waterproofness of the interface. The mixture is transferred to an ultrasonic dispersion device and treated with 200-300W power for 5-10 minutes to obtain a slurry. This process breaks up air bubbles and agglomerates in the slurry, allowing the nano-zinc oxide and graphene to be evenly dispersed, thus improving antibacterial and thermal conductivity properties. Stepwise stirring avoids reaction conflicts between materials and ensures the uniform distribution of functional materials such as bentonite and fibers. After ultrasonic treatment, the porosity of the mixture is reduced to below 8%, laying the foundation for the densification of the board and improving the interfacial bonding between the flame retardant and the matrix.

[0031] Also includes: The slurry is injected into a vacuum degasser and treated at a vacuum of -0.09MPa for 4-5 minutes to remove air bubbles trapped in the slurry, reduce the internal pores of the board after molding, and improve the density and water resistance. The slurry is then pressed into a wet board blank by three rollers. The wet slurry blank is transferred to the curing room and left to stand for 2 hours at 20-25℃ and 30-70% relative humidity, so that the bentonite can initially absorb water and expand to fill the micropores inside the blank. Adjust the temperature of the curing room to 60-80℃ and the relative humidity to 80-90%, and perform hydrothermal curing for 2-4 hours to accelerate the hydration reaction of cement and steel slag powder, generate more CSH gel, and improve the strength of the matrix. After demolding, place the board in a well-ventilated drying area with a temperature of 20-25℃ and a humidity of 50%-60% to air dry naturally for 36-72 hours. Control the drying rate to ≤0.5% / h to avoid cracking caused by rapid drying and ensure dimensional stability. After drying, a 0.2-0.5mm thick silane waterproofing agent is sprayed onto the surface of the board and cured at room temperature for 12-24 hours to form a hydrophobic film on the surface, further improving the waterproof performance and reducing the water absorption rate.

[0032] In summary, the final waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board comprises the following components by weight: The composition includes: 38-55 parts graphene-modified diatomaceous earth, 12-22 parts silicate cement, 6-9 parts bentonite, 4-7 parts steel slag powder, 5-8 parts metakaolin, 3-6 parts modified rice husk fiber, 4-6 parts aluminum hydroxide, 1-2 parts polysiloxane repair agent, 0.8-1.5 parts sodium carboxymethyl cellulose, 0.5-1 part defoamer, and 1-2 parts nano zinc oxide. Graphene-modified diatomaceous earth comprises diatomaceous earth and graphene in a mass ratio of 100:2, and 0.3% titanate coupling agent; Modified rice husk fiber includes lignin- and pectin-free rice husk fiber, 1.5% sodium hydroxide, and 0.5% silane coupling agent; The matrix material consists of graphene-modified diatomaceous earth, silicate cement, steel slag powder, and metakaolin, while the reinforcing material consists of activated bentonite, aluminum hydroxide, and modified rice husk fiber.

[0033] Example 1: This example uses the original scheme as the experimental group as the baseline and sets up 5 control experiments to control variables for graphene-modified diatomaceous earth, modified rice husk fiber, activated bentonite, ultrasonic dispersion, and gradient hydrothermal curing, respectively. The proportions of other raw materials and process steps are kept consistent to verify the advantages of the original scheme.

[0034] In control group 1, ordinary diatomaceous earth without graphene modification was used to replace graphene-modified diatomaceous earth, and the rest was the same as the experimental group; in control group 2, unmodified rice husk fiber was used to replace modified rice husk fiber, and the rest was the same as the experimental group; in control group 3, activated bentonite was removed, and the proportions of other raw materials were the same as the experimental group, with the total number of parts made up by adding silicate cement; in control group 4, the ultrasonic dispersion step was omitted, and the rest was the same as the experimental group; in control group 5, traditional natural curing was used to replace gradient hydrothermal curing, and the rest was the same as the experimental group.

[0035] For sample preparation, three standard specimens of 100mm×100mm×10mm were prepared for each group, and the average value was used for performance testing. The raw material pretreatment, mixing, and molding process were strictly carried out in accordance with the above-disclosed plan and steps.

[0036] Regarding testing indicators, this embodiment uses the three-point bending method to test flexural and compressive strength according to GB / T17671-1999 "Test Method for Strength of Cement Mortar"; it uses the method according to GB / T19979-2005 "Test Method for Water Vapor Permeability of Building Materials and Their Products" to test 24-hour water impermeability by observing wet marks on both sides; it uses the burning time, weight loss rate, and temperature rise to test the flame retardant rating according to GB / T5464-2010 "Test Method for Non-combustibility of Building Materials"; and it uses 0.2mm artificial prefabrication... For the microcracks, after being placed in an environment with 90% humidity for 24 hours, the self-healing efficiency was detected by observing the crack filling rate using SEM; the thermal conductivity was tested according to GB / T10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Protective Hot Plate Method"; the antibacterial rate against Escherichia coli was tested according to GB / T21510-2008 "Test Method for Antibacterial Properties of Nano-Inorganic Materials"; and the dimensional change rate after water absorption was calculated according to GB / T4614-2008 "Determination of Water Absorption of Phenolic Molded Plastics".

[0037] The results are shown below: Table 1 As shown in the table above, the experimental group had 38% and 27% higher flexural and compressive strength than the control group 1, respectively, a 31.4% lower thermal conductivity, and a 13.9% higher formaldehyde purification rate. This demonstrates that graphene modification can significantly improve strength, thermal conductivity, and adsorption performance, and its layered structure enhances flame retardancy and interfacial bonding.

[0038] The experimental group had a 52.4% lower swelling rate than the control group and a 10.7% higher antibacterial rate, indicating that alkali treatment combined with silane coupling agent modification can effectively reduce fiber water absorption while retaining antibacterial function and preventing board cracking.

[0039] The self-healing efficiency of the experimental group (92.3%) was much higher than that of the control group (31.2%), which verifies that the sodium modification of bentonite can achieve self-healing of microcracks through water absorption and expansion, and is the core carrier of self-healing function.

[0040] The experimental group showed a 44.8% lower porosity and a 20% higher flexural strength than the control group, indicating that ultrasonic treatment can effectively break up bubbles and agglomerates, and improve the density and strength of the board.

[0041] The experimental group had a flexural strength 12.1% higher than the control group 5 and a thermal conductivity 5.3% lower, proving that hydrothermal curing at 80℃ can accelerate the cement hydration reaction, generate more CSH gel, and strengthen the matrix structure.

[0042] Example 2: In this example, the following components were used as the baseline: 50 parts graphene-modified diatomaceous earth, 18 parts silicate cement, 8 parts bentonite, 6 parts steel slag powder, 7 parts metakaolin, 5 parts modified rice husk fiber, 5 parts aluminum hydroxide, 1.5 parts polysiloxane repair agent, 1.2 parts sodium carboxymethyl cellulose, 0.5 parts defoamer, and 1.5 parts nano zinc oxide. Five control experiments were set up by selecting the upper and lower limits and the median value of the core components. Only the component parts were changed. The pretreatment process and preparation process of the other raw materials strictly followed the above scheme. The advantages of the baseline group were verified by comparing the key performance indicators.

[0043] The control group 1 was used as the lower limit group, and its components were: 38 parts of graphene modified diatomaceous earth, 12 parts of silicate cement, 6 parts of bentonite, 4 parts of steel slag powder, 5 parts of metakaolin, 3 parts of modified rice husk fiber, 4 parts of aluminum hydroxide, 1 part of polysiloxane repair agent, 0.8 parts of sodium carboxymethyl cellulose, 0.5 parts of defoamer, and 1 part of nano zinc oxide.

[0044] Control group 2, as the upper limit combination, consists of 55 parts graphene-modified diatomaceous earth, 22 parts silicate cement, 9 parts bentonite, 7 parts steel slag powder, 8 parts metakaolin, 6 parts modified rice husk fiber, 6 parts aluminum hydroxide, 2 parts polysiloxane repair agent, 1.5 parts sodium carboxymethyl cellulose, 1 part defoamer, and 2 parts nano zinc oxide. Control group 3 reduced the amount of diatomaceous earth, and its components were: 38 parts graphene-modified diatomaceous earth, 18 parts silicate cement, 8 parts bentonite, 6 parts steel slag powder, 7 parts metakaolin, 5 parts modified rice husk fiber, 5 parts aluminum hydroxide, 1.5 parts polysiloxane repair agent, 1.2 parts sodium carboxymethyl cellulose, 0.5 parts defoamer, and 1.5 parts nano zinc oxide. Control group 4 reduced the amount of cement, and its components were: 50 parts graphene-modified diatomaceous earth, 22 parts silicate cement, 8 parts bentonite, 6 parts steel slag powder, 7 parts metakaolin, 5 parts modified rice husk fiber, 5 parts aluminum hydroxide, 1.5 parts polysiloxane repair agent, 1.2 parts sodium carboxymethyl cellulose, 0.5 parts defoamer, and 1.5 parts nano zinc oxide. Control group 5 reduced the amount of bentonite, and its components were: 50 parts graphene-modified diatomaceous earth, 18 parts silicate cement, 6 parts bentonite, 6 parts steel slag powder, 7 parts metakaolin, 5 parts modified rice husk fiber, 5 parts aluminum hydroxide, 1.5 parts polysiloxane repair agent, 1.2 parts sodium carboxymethyl cellulose, 0.5 parts defoamer, and 1.5 parts nano zinc oxide.

[0045] Three standard specimens (100mm × 100mm × 10mm) were prepared for each group. The pretreatment process and molding and curing procedures were strictly followed according to the original scheme to ensure that all conditions except for the component ratios were consistent. The test standards are as shown in Example 1, and the results are shown in the table below: Table 2 In summary, the preferred embodiment of this application is composed of 50 parts graphene-modified diatomaceous earth, 18 parts silicate cement, 8 parts bentonite, 6 parts steel slag powder, 7 parts metakaolin, 5 parts modified rice husk fiber, 5 parts aluminum hydroxide, 1.5 parts polysiloxane repair agent, 1.2 parts sodium carboxymethyl cellulose, 0.5 parts defoamer, and 1.5 parts nano zinc oxide.

[0046] It should be noted that the descriptions of each embodiment in the above embodiments have different focuses. For parts that are not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.

[0047] Those skilled in the art will understand that embodiments of the present invention can be provided as methods, systems, or computer program products. Therefore, the present invention can take the form of a completely hardware embodiment, a completely software embodiment, or an embodiment combining software and hardware aspects. Furthermore, the present invention can take the form of a computer program product embodied on one or more computer-usable storage media (including, but not limited to, disk storage, CD-ROM, optical storage, etc.) containing computer-usable program code.

[0048] This invention is described with reference to flowchart illustrations and / or block diagrams of methods, apparatus (systems), and computer program products according to embodiments of the invention. It will be understood that each block of the flowchart illustrations and / or block diagrams, as well as combinations of blocks in the flowchart illustrations and / or block diagrams, can be implemented by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, special-purpose computer, embedded computer, or other programmable data processing apparatus to produce a machine, such that the instructions, which execute via the processor of the computer or other programmable data processing apparatus, generate instructions for implementing the flowchart. Figure 1 One or more processes and / or boxes Figure 1 A device that provides the functions specified in one or more boxes.

[0049] These computer program instructions may also be stored in a computer-readable storage medium that can direct a computer or other programmable data processing device to function in a particular manner, such that the instructions stored in the computer-readable storage medium produce an article of manufacture including instruction means, which are implemented in a process Figure 1 One or more processes and / or boxes Figure 1 The function specified in one or more boxes.

[0050] These computer program instructions may also be loaded onto a computer or other programmable data processing equipment to cause a series of operational steps to be performed on the computer or other programmable equipment to produce a computer-implemented process, thereby providing instructions that execute on the computer or other programmable equipment for implementing the process. Figure 1 One or more processes and / or boxes Figure 1 The steps of the function specified in one or more boxes.

[0051] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.

[0052] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board, characterized in that, Includes the following components by weight: The composition includes: 38-55 parts graphene-modified diatomaceous earth, 12-22 parts silicate cement, 6-9 parts activated bentonite, 4-7 parts steel slag powder, 5-8 parts metakaolin, 3-6 parts modified rice husk fiber, 4-6 parts aluminum hydroxide, 1-2 parts polysiloxane repair agent, 0.8-1.5 parts sodium carboxymethyl cellulose, 0.5-1 part defoamer, and 1-2 parts nano zinc oxide. The graphene-modified diatomaceous earth comprises diatomaceous earth and graphene in a mass ratio of 100:2, and 0.3% titanate coupling agent. The modified rice husk fiber comprises lignin- and pectin-free rice husk fiber, 1.5% sodium hydroxide, and 0.5% silane coupling agent. After crushing the calcium-based bentonite ore, a 3% sodium carbonate solution was added, and the mixture was filtered to obtain a filter cake. A 0.3% polyvinyl alcohol solution was added to granulate the cake to obtain activated bentonite. The graphene-modified diatomaceous earth, silicate cement, steel slag powder, and metakaolin form the matrix material, while the activated bentonite, aluminum hydroxide, and modified rice husk fiber form the reinforcing material.

2. The waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board according to claim 1, characterized in that, The diatomaceous earth functional board comprises the following specific components: The ingredients are: 50 parts graphene-modified diatomaceous earth, 18 parts silicate cement, 8 parts bentonite, 6 parts steel slag powder, 7 parts metakaolin, 5 parts modified rice husk fiber, 5 parts aluminum hydroxide, 1.5 parts polysiloxane repair agent, 1.2 parts sodium carboxymethyl cellulose, 0.5 parts defoamer, and 1.5 parts nano zinc oxide.

3. The waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board according to claim 1, characterized in that, The graphene-modified diatomaceous earth has a specific surface area ≥130 m². 2 / g, the moisture swelling rate of the modified rice husk fiber is ≤0.12%.

4. A method for preparing a waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board, applied to the waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board according to any one of claims 1-3, characterized in that, The method includes: using diatomaceous earth ore and graphene as substrates, preparing graphene-modified diatomaceous earth by modification with 0.3% titanate coupling agent; treating the surface of rice husk fibers with alkali; preparing modified rice husk fibers with 0.5% silane coupling agent; using calcium-based bentonite as substrates, modifying it with sodium and then granulating it; using magnetically separated steelmaking waste slag as substrates, preparing steel slag micro powder through pretreatment; and preparing the resulting product into a mixture and molding curing process to obtain a diatomaceous earth functional board. The method also includes the following sub-steps: S101. After crushing the raw diatomite ore, it is initially ground. The initial ground diatomite and graphene are added at a mass ratio of 100:2 and mixed until the graphene adheres to the initial ground diatomite. 0.3% titanate coupling agent and deionized water are added, and the mixture is ultrasonically dispersed. The suspension is dried by a dryer to obtain composite powder. S102. After removing impurities, washing and drying the waste rice husks, crush them into fiber segments, add 1.5% sodium hydroxide to remove surface lignin and pectin, wash and add 0.5% silane coupling agent for modification, ultrasonic treatment, dry and crush again to obtain modified rice husk fiber. S103. After crushing the calcium-based bentonite ore, add 3% sodium carbonate solution, filter to obtain filter cake, add 0.3% polyvinyl alcohol solution to granulate, and obtain activated bentonite. S104. Steelmaking waste slag is magnetically separated to remove iron, then crushed, added with 5% sulfuric acid solution, acid washed, and then added with triethanolamine and stirred to obtain steel slag powder. S105. The obtained dry powder, reinforcing material, liquid and additives are added in sequence and dispersed by ultrasonication to obtain slurry. The slurry is then degassed by vacuum, rolled and cured.

5. The method for preparing a waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board according to claim 4, characterized in that, The method of preparing graphene-modified diatomaceous earth using diatomaceous earth ore and graphene as substrates, and modified with 0.3% titanate coupling agent, further includes: The particle size of the diatomite ore obtained after crushing is ≤5mm, and it is initially ground to 300 mesh using a grinding mill; The added graphene sheets have a diameter of 5-10 μm and a thickness of 0.8-1.2 nm; The diatomaceous earth and graphene were mixed under a stirring environment of 2000-5000 rpm for 5-10 min to obtain a mixed powder in which graphene was attached to the diatomaceous earth. Add 0.3% titanate coupling agent and deionized water to prepare a 30-40% suspension of mixed powder, and sonicate for 30-45 minutes. The suspension was dried in a spray dryer, and the resulting composite powder was pulverized by airflow at an air pressure of 1.1-1.3 MPa and screened as graphene-modified diatomaceous earth with a mesh size of 1200-1500.

6. The method for preparing a waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board according to claim 4, characterized in that, The process of treating the surface of rice husk fibers with alkali and preparing modified rice husk fibers using 0.5% silane coupling agent further includes: The waste rice husks, after being cleaned and purified, are dried in an oven at 90-105℃ until the moisture content is ≤5%, and the fiber segments shredded by the shredder are 5-10mm in length. Add 1.5% sodium hydroxide solution to the fiber segment at a solid-liquid ratio of 1:10, and stir and cook in a water bath at 60-80℃ for 25-40 minutes. Wash with deionized water at pH 7 until the fiber segments are neutral, filter, add 0.5% silane coupling agent at a solid-liquid ratio of 1:8, sonicate for 20-30 minutes, dry at 45-60℃, and then pulverize the fiber segments to a mesh size greater than 350.

7. The method for preparing a waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board according to claim 4, characterized in that, The process of granulation after sodium modification using calcium-based bentonite as a substrate further includes: The calcium-based bentonite ore is crushed and sieved through a 200-mesh sieve. A 3% sodium carbonate solution is added at a solid-liquid ratio of 1:6, and the mixture is stirred at 50-60℃ for 2-4 hours for sodium modification. After standing and settling for 3-4 hours, the filter cake is filtered, dried at 70-80℃, and pulverized to 300 mesh. A 0.3% polyvinyl alcohol solution is added at a solid-liquid ratio of 1:5 for granulation.

8. The method for preparing a waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board according to claim 4, characterized in that, The method of preparing steel slag powder through pretreatment using magnetically separated steelmaking waste slag as a substrate further includes: Steelmaking waste slag removed by magnetic separation is crushed to 400 mesh, soaked in 5% sulfuric acid solution at a ratio of 1:4 for 1-3 hours, acid washed and washed with deionized water until neutral, dried at 100-115℃ and stirred with 0.2% triethanolamine for 4-12 minutes.

9. The method for preparing a waterproof, flame-retardant, dense, environmentally friendly diatomaceous earth functional board according to claim 4, characterized in that, The obtained product is then subjected to mixture preparation and molding curing, including: Graphene-modified diatomaceous earth, ordinary silicate cement, steel slag powder, and metakaolin are added to a twin-shaft mixer and stirred at 100-300 r / min for 5-10 min at room temperature. Add activated bentonite, aluminum hydroxide, and modified rice husk fiber, adjust the speed to 200-400 r / min and continue stirring for 2-5 min to embed it into the powder skeleton; Add polysiloxane repair agent, sodium carboxymethyl cellulose, and nano zinc oxide, and add 40-48% deionized water by weight. Heat to 55-60℃ and stir at 100-200 r / min for 15 min. The mixture is transferred to an ultrasonic dispersion device and processed at 200-300W power for 5-10 minutes to obtain a slurry.

Citation Information

Patent Citations

  • Environment-friendly multifunctional diatom plate with moisture resistance, water resistance and flame retardance, and preparation method of diatom plate

    CN113045265A

  • Graphene oxide modified diatomite fireproof thermal insulation board

    CN112028554A

  • Repairing material for cracks accompanied with water leakage in concrete structure and process for repairing said cracks using said repairing material

    WO2013005677A1